2021
DOI: 10.1080/21505594.2021.1950955
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of publicly available Hungatella hathewayi genomes revealed genetic distances indicating they belong to more than one species

Abstract: Torres (2021) Analyses of publicly available Hungatellahathewayi genomes revealed genetic distances indicating they belong to more than one species

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Genetic distance is one of the common indicators of genetic differentiation among plant populations [ 56 ]. In the present study, we found that the genetic distance between the wild ancient tea tree populations at adjacent altitudes was small, and genetic distance over large altitude difference was larger.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic distance is one of the common indicators of genetic differentiation among plant populations [ 56 ]. In the present study, we found that the genetic distance between the wild ancient tea tree populations at adjacent altitudes was small, and genetic distance over large altitude difference was larger.…”
Section: Discussionmentioning
confidence: 99%
“…The pangenome analysis indicated that the strains described herein should be considered as new species. Additionally, the genetic distance cut-off (OrthoANI values) and core genes similarity (%) should be established for Bartonella , as previously conducted for Hungatella hathewayi , a necessary step toward evaluating the intrageneric diversity [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Isolates were selected and the gDNA was extracted after lysis using Qiagen DNeasy blood and tissue kits [ 14 ]. Each sample was used to produce a sequencing library with gDNA that was of sufficient quality (A 260/280 and A 260/230 > 1.5) with an average insert size of 350 bp according to the KAPA HyperPlus Kit protocol as described previously [ 16 , 17 , 18 , 19 ]. All samples were sequenced using HiSeq XTEN Sequencing System (Illumina, San Diego, CA, USA) [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…WGS was performed using the methods from the 100K Pathogen Genome Project [ 14 , 15 ]. Briefly, high-molecular-weight genomic DNA (gDNA) was extracted from banked bacterial isolate colonies using the Wizard Genomic DNA Jit (Promega, Madison, WI; cat#A1460) as described previously [ 16 ].…”
Section: Methodsmentioning
confidence: 99%